2021
DOI: 10.24198/jkg.v33i1.30751
|View full text |Cite
|
Sign up to set email alerts
|

<p>Potensi ekstrak daun singkong (Manihot esculenta Crantz.) terhadap profil leukosit darah tepi model tikus disfungsi ovarium dan periodontitis</p><p>Potential of cassava leaves (Manihot esculenta Crantz.) extract on peripheral blood leukocyte profile in ovary dysfunction and periodontitis rat model</p>

Abstract: Pendahuluan: Disfungsi ovarium merupakan keadaan ovarium yang mengalami kegagalan dalam sekresi hormon seks steroid. Penurunan sekresi hormon terutama estrogen dapat memicu peningkatan sitokin proinflamasi seperti IL-1, IL-6 dan TNF-α yang berperan dalam resorpsi tulang dan reaksi inflamasi periodontal. Salah satu drug of choice dari periodontitis adalah metronidazole. Penggunaan metronidazole secara sistemik dapat mengakibatkan efek samping, sehingga diperlukan bahan alternatif yang memiliki efek terapi antii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This means that cassava leaf extract administration can enhance fibroblast quantity and collagen density. This increase is believed to be related to the active chemical compound of cassava leaves such as flavonoids, tannins, saponins, triterpenoids, and vitamin C. 22 According to Meilawaty and Kusumawardani (2016), cassava leaf extract can reduce expression of the proinflammatory cytokines TNF-α and cyclooxygenase-2 (COX-2). 20 Another study also showed that cassava leaf extract could reduce MMP-8 expression in rats with ovarian dysfunction with P. gingivalis -induced periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that cassava leaf extract administration can enhance fibroblast quantity and collagen density. This increase is believed to be related to the active chemical compound of cassava leaves such as flavonoids, tannins, saponins, triterpenoids, and vitamin C. 22 According to Meilawaty and Kusumawardani (2016), cassava leaf extract can reduce expression of the proinflammatory cytokines TNF-α and cyclooxygenase-2 (COX-2). 20 Another study also showed that cassava leaf extract could reduce MMP-8 expression in rats with ovarian dysfunction with P. gingivalis -induced periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Then the solution was concentrated using a rotary evaporator set to 50 °C and 90 rpm, allowing the semi-solid cassava leaf extract to be obtained. 22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation